Comparação de sistemas agroflorestais em assentamentos rurais: estudo de caso nos municípios de Bonito e Ponta Porã - MS - Francisco, Priscila Maria Silva (2016)
In an area with high biodiversity of the native vegetation of savannah and Atlantic forest as the studied areas of the state of Mato Grosso do Sul, the systems agroflorestais should present models to propitiate the maintenance of that biodiversity and guarantee the family farmers' alimentary sovereignty. In that expectation, it was aimed at in this study to compare the implantation and transport of systems agroflorestais among two areas with different ecotones, in order to recognize potentialities to promote the recovery of degraded areas. For the collection of data an itinerary half structured was applied containing closed and open subjects. The lifted up information in the units of production refer to items as: i) the farmers' characterization as for the socket of decision as for the handling of SAFs and to the size of the unit of production and of SAF; ii) implantation of the systems: reasons of the implantation and objectives; iii) I handle of the system agroflorestal; iv) commercialization; v) technical support; and I saw) public politics disputed by the farmers that supported the implementation of SAFs of agroecological bases. The obtained data were systematized and analyzed in the Software Statistical Package goes Social the Sciences. SPSS. It was contacted that, the ecorregiões the socket of decision as for the handling of the system it leaves of the masculine gender, that you/they need improvements in relation to the technical support and of support and incentives for investment in infrastructure to process the production originating from of the systems agroflorestais in order to join value to the final product. The insert type to the market and the government's programs like PAA and PNAE influences strongly in those farmers' income, therefore they are necessary public politics that you/they think the production and the commercialization of the products, offering support for the construction of fairer markets.